KEPEMIMPINAN TRANSFORMASIONAL SEBAGAI SOLUSI PENGEMBANGAN KONSEP SMART CITY MENUJU ERA SOCIETY 5.0: SEBUAH KAJIAN LITERATUR [TRANSFORMATIONAL LEADERSHIP AS A SOLUTION FOR THE DEVELOPMENT OF THE SMART CITY CONCEPT IN THE SOCIETY ERA: A LITERATURE REVIEW] - Ardinata, Rayhand Putra; Rahmat, Hayatul Khairul; Andres, Frans Serano; Waryono, W (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2022)
The emergence of the concept of the era of society 5.0 which is a development of the era of the industrial revolution 4.0 which puts people forward as a source of innovation and cannot be separated from technology makes human problems in urban areas easier to solve, one of which is the concept of a smart city. To realize a smart city requires an innovative and transformative leader. Therefore, this paper aims to examine transformational leadership as a solution for developing the smart city concept in the era of society 5.0. The writing method used is a literature study. The findings of this study are transformational leadership or known as smart integrated leadership is one solution to realize the smart city concept in the era of society 5.0 because this leadership model is able to bring change to the era of society 5.0 by prioritizing three important aspects, namely smart people, smart governance and smart infrastructure, technology and environment.